2011
DOI: 10.1103/physreva.84.042310
|View full text |Cite
|
Sign up to set email alerts
|

Remote information concentration and multipartite entanglement in multilevel systems

Abstract: Remote information concentration (RIC) in d-level systems (qudits) is studied. It is shown that the quantum information initially distributed in three spatially separated qudits can be remotely and deterministically concentrated to a single qudit via an entangled channel without performing any global operations. The entangled channel can be different types of genuine multipartite pure entangled states which are inequivalent under local operations and classical communication. The entangled channel can also be a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 98 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…The drawbacks of this method are that lots of entanglement resources are needed and a coherent operation on a large Hilbert space including all states is necessary. It is already shown that bound entanglement can be used as a resource in quantum information concentration [34], and some different schemes are also proposed in some contexts [35][36][37][38].…”
Section: Quantum Information Concentration In the Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawbacks of this method are that lots of entanglement resources are needed and a coherent operation on a large Hilbert space including all states is necessary. It is already shown that bound entanglement can be used as a resource in quantum information concentration [34], and some different schemes are also proposed in some contexts [35][36][37][38].…”
Section: Quantum Information Concentration In the Networkmentioning
confidence: 99%
“…The drawbacks of this method are that lots of entanglement resources are needed and a coherent operation on a large Hilbert space including all states is necessary. Some different schemes are proposed in some contexts [31][32][33][34][35].…”
mentioning
confidence: 99%
“…Henceforth, more and more people devote themselves to studying in this field. In recent years, RQIC has been generalized to many-particle and high-dimensional systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A scheme for implementing the reversal of the optimal 1→2 universal telecloning via a four-qubit Greenberger-Horne-Zeilinger (GHZ) state [21] has also been proposed [22]. Recently, RQIC has been generalized to many-particle and high-dimensional systems [23][24][25].…”
Section: Introductionmentioning
confidence: 99%